Fast initial position of the shaft permanent magnet motor IPMSM - Kasprowicz, A.; Tocha, M. (Scientific Journal of Gdynia Maritime University, 2017)
The article presents the method and results of experimental research on an algorithm of the instant estimation of an initial position of the rotor of the permanent magnet motor. It is part of the design of highly dynamic controlled AC drive. Estimation and drive control algorithm has been implemented in the driver of the new generation signal microcontroller TMS320F28335 of Texas Instrument. It was written in C. The algorithm has proved itself in a model system of the drive. The estimation of the initial position of the shaft of the permanent magnet motor helped to reduce the cost and complexity of the drive system. Thanks to it, a cheaper and more convenient to use incremental encoder could be used. Without the estimation, however, it did not ensure the initial position of the rotor, required to proper start and work of the motor.